Acute whole body UVA irradiation combined with nitrate ingestion enhances time trial performance in trained cyclists - Muggeridge, D. J.; Sculthorpe, N.; Grace, F. M.; Willis, G.; Thornhill, L.; Weller, R. B.; James, P. E.; Easton, C. (Nitric Oxide, 2015)
Dietary nitrate supplementation has been shown to increase nitric oxide (NO) metabolites, reduce blood pressure (BP) and enhance exercise performance. Acute exposure to ultraviolet (UV)-A light also increases NO bioavailability and reduces BP. We conducted a randomized, counterbalanced placebocontrolled trial to determine the effects of UV-A light alone and in combination with nitrate on the responses to sub-maximal steady-state exercise and time trial (TT) performance. Nine cyclists (VO2max 53.1 ± 4.4 ml/ kg/min) completed five performance trials comprising 10 min submaximal steady-state cycling followed by a 16.1 km TT. Following a familiarization the final four trials were preceded, in random order, by either (1) Nitrate gels (NIT) + UV-A, (2) Placebo (PLA) + UV-A, (3) NIT + Sham light (SHAM) and (4) PLA + SHAM (control). The NIT gels (2 × 60 ml gels, ~8.1 mmol nitrate) or a low-nitrate PLA were ingested 2.5 h prior to the trial. The light exposure consisted of 20 J/cm2 whole body irradiation with either UV-A or SHAM light. Plasma nitrite was measured pre- and post-irradiation and VO2 was measured continuously during steady-state exercise. Plasma nitrite was higher for NIT + SHAM (geometric mean (95% CI), 332 (292- 377) nM; P = 0.029) and NIT + UV-A (456 (312-666) nM; P = 0.014) compared to PLA + SHAM (215 (167- 277) nM). Differences between PLA + SHAM and PLA + UV-A (282 (248-356) nM) were small and nonsignificant. During steady-state exercise VO2 was reduced following NIT + UVA (P = 0.034) and tended to be lower in NIT + SHAM (P = 0.086) but not PLA + UV-A (P = 0.381) compared to PLA + SHAM. Performance in the TT was significantly faster following NIT + UV-A (mean ± SD 1447 ± 41 s P = 0.005; d = 0.47), but not PLA + UV-A (1450 ± 40 s; d = 0.41) or NIT + SHAM (1455 ± 47 s; d = 0.28) compared to PLA + SHAM (1469 ± 52 s). These findings demonstrate that exposure to UV-A light alone does not alter the physiological responses to exercise or improve performance in a laboratory setting. A combination of UV-A and NIT, however, does improve cycling TT performance in this environment, which may be due to a larger increase in NO availability.